Investigation of Site-Specific Shear Wave Velocity for Geotechnical Engineering Applications Using Microtremor Array Measurement - Nazri, F.M.; Tan, Chee Ghuan; Ramli, M.Z. (Springer Verlag, 2016)
Microtremor array measurement surveys were performed in three locations to determine the shear wave velocity profile down to a depth of 30 m. The shear wave velocity results from the data acquisition of the multichannel surface wave method were compared with the microtremor array measurement in terms of the shear wave velocity profile as a function of depth. The correlation indicated that the shear wave velocity values range from 200 to 300 m/s and showed a significant velocity contrast at a shallow depth.